Improved understanding of the spatially-heterogeneous relationship between satellite solar-induced chlorophyll fluorescence and ecosystem productivity - Yang Song (Elsevier, 2021)
Satellite solar-induced chlorophyll fluorescence (SIF) is deemed as a good proxy for vegetation photosynthesis. To date, SIF has been shown to correlate strongly with gross primary productivity (GPP) at ecosystem scale and perform well in monitoring the impacts of extreme climate events on ecosystem productivity. However, the SIF-GPP relationship exhibits a spatially-heterogeneous pattern across ecosystems and produces both linear and nonlinear results at different spatiotemporal scales. Understanding of the different spatiotemporal SIF-GPP relationships is still incomplete and somewhat controversial in previous studies. Here, based on the light-use efficiency (LUE) models, this study investigated the spatially-heterogeneous SIF-GPP relationships across the conterminous United States (CONUS), and examined the possible drivers and mechanisms. Our results showed that SIF and GPP exhibited similar spatiotemporal patterns but responded differently to environmental factors (i.e., soil moisture, precipitation, photosynthetically active radiation, air temperature, and atmospheric vapor pressure deficit). The correlation analysis showed that the SIF-GPP relationships were spatially-heterogeneous across the CONUS both at monthly and annual scales. Moreover, our findings also indicated that different biome types could partly explain the spatial heterogeneity of SIF-GPP relationship. Different canopy structures and vegetation coverages across biomes could be primary drivers of the spatially-heterogeneous SIF-GPP relationship. In addition, the SIF-GPP relationships under the baseline and drought scenarios appeared to be similar and consistent. It implies that there could be an invariant SIF-GPP relationship under both drought and non-drought conditions, leading to a weak effect of interannual drought on the spatial heterogeneity. In summary, our results highlight that the effects of biome characteristics (Ωbiome) and environmental stresses (Φstress) on spatially-heterogeneous SIF-GPP relationship and further explore possible mechanisms of the linkage between SIF and GPP.